Ants of the genus Lordomyrma Emery (2) The Japanese L. azumai (Santschi) and six new species from India, Viet Nam and the Philippines (Hymenoptera: Formicidae: Myrmicinae) - Taylor, Robert W. (Zootaxa, 2012)
Lordomyrma is recorded for the first time from India and mainland southeast Asia. The Japanese L. azumai is reviewedand six new worker-based species described: L. lakshmi (Kerala State, India); L. hmong (Lao Cai Province, Vietnam); L.diwata, L. emarginata and L. idianale (Mt Isarog, Luzon, Philippines) and L. limatula (Leyte, Philippines). Gynes are characterized for L. azumai, L. hmong and L. limatula. All taxa are diagnosed, illustrated, and their affinities discussed.